Managing the digital transformation : aligning technologies, business models, and operations - Queiroz, Maciel M.; Wamba, Samuel Fosso (Boca Raton, FL : CRC Press, 2023)
"Managing the Digital Transformation provides frameworks and models to support digital transformation projects. The book presents the importance of digital transformation as a resilience approach to the operations processes and business models. It covers the essential elements integrating the technology, the organizations, the operations, and supply chain management used to move towards digital transformation. Concepts and mini-case studies are included to provide a deeper understanding of digital transformation projects with a holistic view. The book also examines the role that digital transformation plays with consideration of inter-organizational and intra-organizational capabilities, along with the role of digital culture, the worker's skills, business models, reconfiguration, as well as an operations optimization angle"--
OCLC-licensed vendor bibliographic record.
Keywords: Management information systems; Industrial management -- Planning; Business planning; TECHNOLOGY / Operations Research; BUSINESS & ECONOMICS / Production & Operations Management